Revisiting Childhood: A Phenomenological Study on Art Students' Lived Experiences of Memory and Fantasy Drawings (European Journal of Behavioral Sciences, 2024)
This phenomenological study explored art students' lived experiences of creating memory and fantasy drawings of their childhood. In-depth semi-structured interviews were conducted with 12 undergraduate art students who completed a drawing assignment revisiting their childhoods through memory and fantasy renderings. Data were analyzed using interpretative phenomenological analysis to extract themes and insights into the essence of the phenomenon. Findings revealed that memory drawings evoked vivid recreations of specific moments and relationships from childhood, eliciting emotional responses ranging from nostalgia to distress. Fantasy drawings provided opportunities for imaginative reworking of childhood experiences, allowing expression of latent wishes, fears, and curiosity. The act of rendering childhood memories and fantasies in visual form allowed access to embodied aspects of past experience and enabled new perspectives. Participants described the assignment as an insightful rediscovery and reevaluation of childhood. The study provides an enhanced understanding of how memory and fantasy drawings provide evocative access to lived dimensions of childhood among art students. The visual articulation and symbolic processing of remembered and imagined childhood experience facilitated self-reflection, emotional exploration and integration.